The Pregnancy Diagnosis in Buffalo Species: Laboratory Methods - Barbato, Olimpia; Barile, Vittoria Lucia (Journal of Buffalo Science, 2012)
Pregnancy diagnosis plays an important role in the reproduction management of ruminants since embryonic mortality has a substantial impact on the fertility of a herd. Most of the embryonic losses occur during the first days after fertilization and during the process of implantation. So it is very important to discriminate, with an early pregnancy diagnosis, non-pregnant from pregnant animals. Hormone analysis to detect pregnancy may be utilize as a more simple technique as an alternative of rectal palpation or ultrasound. In the last years, a large polymorphic family of placenta-expressed proteins has been discovered in ruminant species and used for pregnancy diagnosis. Members of this family are named pregnancy-associated glycoproteins (PAG), being synthesized in the mono-and binucleate cells of the ruminant’s trophectoderm. Part of them is released in the maternal blood circulation where they can be assayed by different laboratory techniques. Due to large variety of expressed molecules and to large variations in the post-translational processing of the PAG, different immuno-systems present different ability to quantify the PAG released in blood. The assay of PAG can also bring very interesting information for researchers working in programs focused on the study of embryonic and fetal mortalities, as well as on embryo biotechnology, animal nutrition or infections diseases resulting in pathologies affecting the pregnancy.